2013
DOI: 10.1371/journal.pone.0056091
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Bovine TB Risk Behaviour amongst Meat Handlers in Nigeria: A Cross-Sectional Study Guided by the Health Belief Model

Abstract: BackgroundBovine Tuberculosis (bTB) is still a serious public health threat in developing countries. The aim of this study is to determine the social and cognitive factors predicting one of the risk behaviours amongst meat handlers in Nigeria, namely, eating Fuku Elegusi. This is the practice of eating the visibly infected parts of the lung in-order to convince customers to buy meat. The study is guided by the health belief model (HBM).MethodsThis is a cross-sectional study of 349 randomly selected meat handle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 14 publications
6
36
3
Order By: Relevance
“…The higher seropositivity of Brucella infection among pregnant women showed by this study could be attributed in part due to the preference for raw foodstuffs like fresh milk, raw meat, and raw animal blood. Eating habits may expose an individual to Brucella infection if the consumed products from infected livestock are not properly prepared [12,18,21,22]. A substantial number of participants in the current study reported a preference for animal fresh milk (73.2%), preference for raw meat (24.3%) and preference for raw animal blood (55.6%).…”
Section: Discussionmentioning
confidence: 80%
“…The higher seropositivity of Brucella infection among pregnant women showed by this study could be attributed in part due to the preference for raw foodstuffs like fresh milk, raw meat, and raw animal blood. Eating habits may expose an individual to Brucella infection if the consumed products from infected livestock are not properly prepared [12,18,21,22]. A substantial number of participants in the current study reported a preference for animal fresh milk (73.2%), preference for raw meat (24.3%) and preference for raw animal blood (55.6%).…”
Section: Discussionmentioning
confidence: 80%
“…Despite the name, many other animals, including humans, are susceptible to infection with M. bovis and humans typically become infected following consumption of animal products contaminated with the bacterium or via close interaction with an infected animal (Muller et al., ; Perez‐Lago, Navarro, & Garcia de Viedma, ). The inhalation of contaminated aerosols usually results in pulmonary TB, whereas ingestion of contaminated products often results in an extra‐pulmonary infection (Hambolu, Freeman, & Taddese, ).…”
Section: Resultsmentioning
confidence: 99%
“…Through the FGDs it was noted that most people are at least involved in one practice placing them at risk of bTB or other zoonotic diseases such as brucellosis. The risky practices that are characteristic of pastoral communities particularly in sub-Saharan Africa included consumption of raw (soured milk) or undercooked meat, poor handling practices and absence of trained veterinary personnel during slaughtering of animals [29– 31]. Most of the participants indicated that they consumed boiled milk, but this practice might have been overstated due to awareness by the participants of the accepted practice.…”
Section: Discussionmentioning
confidence: 99%